Seorang Laki-laki 25 Tahun dengan Trauma Tertutup Bola Mata: Laporan Kasus - Muhammad Yusran; Dhea Novita (CV. Jasa Sukses Abadi, 2021)
Ocular trauma is one of ophthalmologic emergency cases. Trauma to the eye that is not treated immediately can leads to various eye injuries such as visual impairment that can leads to blindness. Mr. AM, 25 years old was admitted to hospital due to blurry vision on the left eye since 6 days ago after fell from height of 5 meters on his workplace. The patient also complaints pain, difficulty to open the left eye and headache. The ophthalmological status obtained anisocoria pupil, visual acuity was 6/60 on the right eye and 3/60 on the left eye. Examination on the right eye revealed superior and inferior palpebral hematoma and conjunctival injection. Examination on the left eye revealed ptosis, superior palpebral hematoma, and abrasion on inferior palpebral. Examination of the extra ocular movements revealed limit eye movement to superior, superolateral, medial, inferior, inferomedial and inferolateral of the left eye. Funduscopy examination shows normal findings. Orbital CT Scan result showed multiple fractures of medial wall of the orbit, frontal bone, and left temporal bone with left frontal intracerebral hematoma, left temporal subdural hematoma, intrasinus hematoma at maxillary, left ethmoid, sfenoid, and frontal sinus. The treatment given to this patient are bed rest with 30 degrees head elevation and warm compresses and the medication taken are ranitidin 2 x 50 mg and metilprednisolon 4 x 250 mg.